Customer segmentation on hotel loyalty programs: leveraging loyalty with data mining - Caetano, Joana Maria Pereira Lupi (2020)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence